Motifs of Woman which Emphasise on the Fertility Goddesses in Elam Civilization (2700-640 BC) - Alizadeh, Siyamak; Jabari, Foroogh (Journal of History Culture and Art Research, 2017)
Woman, earth, moon, snake and cattle were considered as a symbol of fertility in ancient culture believes and each of these elements’ icons is found in the remaining texts from this period. Symbols of women are complex and have usually a twofold role. She is the virgin paradise queen and also rapacious and prostitutes. She has both the characteristics of pure spiritual guidance and also temptation. It is completely apparent that woman has a reproductive role. It is emphasized on reproductive organs of terra-cotta of goddesses that remains from the ancient times. Manufacturing practices, terra-cotta relevant to female and fertility and their comparison with civilization between two rivers were studied by some questions such as the circumstances of the process of evolution and development of terra-cotta in the respect of shape and concept. It is tried to consider the aspects and use the primary sources as far as possible. So, ritual applications, the method of Elamate thinking about woman and also social status of women in the foundations of Elamate thinking were determined.